The Influence of Promotion and Wedding Package Prices on Sales Volume at Happy Bali Wedding - Wahyuni, Ni Made Melia Prashanti; Citrawati, Luh Putu; Sumadi, I Gede (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to find out and analyse the influence of promotions and wedding package prices on sales volume at Happy Bali Wedding. The data analysis technique used was quantitative descriptive through a statistical approach using a questionnaire and analysed by multiple linear regression, classical assumption test, individual parameter significance test (t-test), simultaneous significance test (F test) and determination coefficient R2. The number of samples taken was 74 respondents. The results of the research and discussion, the tcount value for X1 (5.667) > ttable (1.996) and the significance level of 0.000 < 0.05 and the tcount value for X2 (8.242) > ttable (1.996) and the significance level of 0.000 < 0.05, which means that partially the promotion variable (X1) and the wedding package price variable (X2) have a positive effect and significant to sales volume (Y). Based on the results of the F Test, it was shown that the F value calculated > F table (810.247 > 3.15) which means promotion (X1) and wedding package price (X2) simultaneously against sales volume (Y). From these results, it is known that promotions and wedding package prices are obtained the result of the influence of independent variables (X1 and X2) on the dependent variable (Y) that can be explained by the regression equation is 95.8%, while the remaining 4.2% is influenced by other factors that are not studied.